Image de-Noising by Selective Filtering Based on Double-Shot Pictures - Florencio, Dinei (ICIP, 2005)
The quality of photographs is often reduced by sensor noise. This was a problem with film cameras, and is still a problem with current CCD and CMOS sensors, particularly in low-lighting conditions. De-noising techniques do not always perform satisfactorily. Typical de-noise techniques reduce the sharpness of the image. In this paper we propose a new de-noising technique, which is based on a dual-shot technique. The proposed algorithm is based on selectively removing high frequencies that do not correlate well between the frames. The algorithm borrows from video processing noise-removal techniques, but the final picture is derived from filtering a single shot, avoiding doublecontouring and other artifacts that may happen with video techniques. While the decision is made based on both frames, the filtering itself is done using exclusively one of the frames. For this reason, the second (auxiliary) shot may be of much lower quality.